Pengaruh Bauran Pemasaran (7P) Terhadap Kepuasan Pelanggan Pada Salon Murti Jepara - Agus Susanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Salon Murti is a beauty salon located in Guyangan Village, RT 1 RW 5, South District, Kamdowo Field, Bangsri District, Jepara Regency, Central Java. Salon Murti has a line of business: beauty salon, hair care, facial care and bridal make-up. Mrs. Sri Murti is the owner of Salon Murti. Salon Murti, even though it is located in a village, can develop rapidly. The development of the bridal makeup studio and beauty salon is supported by Mrs. Sri Murti's ability to develop salons using the Marketing Mix (7P) marketing strategy, namely product, price, place, promotion, people or HR. (People), Physical appearance (Physical Evidence), 2 Process (Process) in providing satisfaction to customers. Mrs. Murti always tries to develop her salon business, including by developing a place. Salon Murti is trying to develop its product services by opening a beauty salon service business, hair care, facial care and bridal make-up. The place is developed for the convenience of customers. Both for waiting rooms and treatment rooms, Salon Murti The aim of this research is to test and analyze the effect of the marketing mix (7P) on customer satisfaction at Salon Murti Jepara.